Survival after traumatic brain injury improves with deployment of neurosurgeons: a comparison of US and UK military treatment facilities during the Iraq and Afghanistan conflicts. Issue 4 (7th February 2020) - Breeze, John; Bowley, Douglas M; Harrisson, Stuart E; Dye, Justin; Neal, Christopher; Bell, Randy S; Armonda, Rocco A; Beggs, Andrew D; DuBose, Jospeh; Rickard, Rory F; Powers, David Bryan
Abstract : Introduction: Traumatic brain injury (TBI) is the most common cause of death on the modern battlefield. In recent conflicts in Iraq and Afghanistan, the US typically deployed neurosurgeons to medical treatment facilities (MTFs), while the UK did not. Our aim was to compare the incidence, TBI and treatment in US and UK-led military MTF to ascertain if differences in deployed trauma systems affected outcomes. Methods: The US and UK Combat Trauma Registries were scrutinised for patients with HI at deployed MTFs between March 2003 and October 2011. Registry datasets were adapted to stratify TBI using the Mayo Classification System for Traumatic Brain Injury Severity. An adjusted multiple logistic regression model was performed using fatality as the binomial dependent variable and treatment in a US-MTF or UK-MTF, surgical decompression, US military casualty and surgery performed by a neurosurgeon as independent variables. Results: 15 031 patients arrived alive at military MTF after TBI. Presence of a neurosurgeon was associated with increased odds of survival in casualties with moderate or severe TBI (p<0.0001, OR 2.71, 95% CI 2.34 to 4.73). High injury severity (Injury Severity Scores 25–75) was significantly associated with a lower survival (OR 4×10 4, 95% CI 1.61×10 4 to 110.6×10 4, p<0.001); however, having a neurosurgeon present still remained significantly positively associated with survival (OR 3.25, 95% CI 2.71 to 3.91, p<0.001). Conclusions: Presence of neurosurgeons increased the likelihood of survival after TBI. We therefore recommend that the UK should deploy neurosurgeons to forward military MTF whenever possible in line with their US counterparts.